Compressive and Flexural Strengths of Bio-Recycled Concrete Incorporated with Kenaf Fibre - Muyideen Abdulkareem; Fadilat Ayeronfe; Taha M. Jassam; Ali H. AlAteah; Khaled A. Alawi Al-Sodani; Mohammed M.H. Al-Tholaia; Hok Yam; Abideen Ganiyu; Sophia C. Alih (Journal of Natural Fibers, 2024)
Kenaf fiber (KF) has been applied in concrete to compensate for the weak tensile strength. Similarly, recycled concrete aggregate (RCA) is applied to reduce problems associated with waste concrete materials. However, both KF and RCA reduce the compressive strength (fck) of concrete. This study involves addition of calcite-producing bacillus subtilis bacteria to recycled aggregate concrete (RAC) incorporated with KF. The bacteria is added to concrete with varying proportions of RCA and KF to produce bio-fibrous recycled concrete (BFRC). The proportions of RCA are 0%, 25% 50% and 75% replacement of coarse aggregate, while KF are 0.2%, 0.5% and 1% of concrete. W/C of 0.45, 0.5, and 0.6 are applied to evaluate the effects of different w/c ratios. The properties evaluated are the fck and the flexural strength (ft) of the concrete samples at 28 days. The results showed that 0.2% KF in bio-concrete (BC) increases the fck by 12%; however, increasing above 0.2% decreases fck. KF in BC increases ft by 60%. Furthermore, 0.5% KF content resulted in highest ft of BRC. Increasing RCA content in bio-recycled concrete and BFRC decreases fck by 30% and 33%, respectively, as well as ft by 13% and 18%, respectively.